Influence of time-of-day on neuromuscular performance in team sport athletes: a systematic review and meta-analysis - Martin-López, Julio; Pérez-López, Alberto; Varillas-Delgado, David; López-Samanes, Álvaro (Frontiers in Sports and Active Living, 2025)
IntroductionAlthough circadian rhythms have been shown to influence some neuromuscular performance tasks, the time-of-day effect on team sports performance athletes remains equivocal. This study aimed to examine the existing evidence concerning diurnal variations in neuromuscular performance in professional and semi-professional team sports athletes using a meta-analytic approach.MethodsA literature search was conducted through three different databases: PubMed, SportDiscus and Web of Science. Article selection was made based on the following inclusion criteria: team sports athletes, professional or semi-professional athletes, neuromuscular performance, testing protocols and time-of-day testing times. Neuromuscular performance parameters such vertical jump capacity (i.e., squat and countermovement jump), agility and isometric strength were included in the analysis. Testing protocols that specifically assessed these parameters across morning (AM) and late afternoon/evening (PM) periods were considered were extracted from the selected studies.ResultsTen studies met the inclusion criteria for qualitative synthesis and five for quantitative synthesis. Meta-analysis indicated lower countermovement jump in the AM compared to with PM (mean difference, −1.44; 95% CI −2.80 to −0.08; p = 0.04) and higher agility performance (mean difference 0.42; 95% CI 0.09–0.74; p = 0.01) in PM comparing with AM. No differences were reported in isometric strength and squat jump performance (p > 0.05).ConclusionNeuromuscular performance is higher in the late afternoon or early evening compared to morning schedules in team sport athletes. Hence, time-of-day variations need to be considered when evaluating neuromuscular performance in professional and semi-professional team sports athletes.